2007
DOI: 10.1111/j.1471-4159.2007.05013.x
|View full text |Cite
|
Sign up to set email alerts
|

CHL1 promotes Sema3A‐induced growth cone collapse and neurite elaboration through a motif required for recruitment of ERM proteins to the plasma membrane

Abstract: Close homolog of L1 (CHL1) is a transmembrane cell adhesion molecule with unique developmental functions in cortical neuronal positioning and dendritic projection within the L1 family, as well as shared functions in promotion of integrin‐dependent neurite outgrowth and semaphorin3A (Sema3A)‐mediated axon repulsion. The molecular mechanisms by which CHL1 mediates these diverse functions are obscure. Here it is demonstrated using a cytofluorescence assay that CHL1 is able to recruit ezrin, a member of the ezrin‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 49 publications
1
53
1
Order By: Relevance
“…In support of this notion, it is interesting to note that secreted CHL1 ectodomain acts as a potent stimulator of neurite outgrowth in vitro (50). Notably, CHL1 interacts with semaphorin 3A during neurite outgrowth and growth cone collapse (53,54). Intriguingly, soluble L1 converts Sema3A-induced axonal repulsion into attraction (55,56).…”
Section: Discussionmentioning
confidence: 83%
“…In support of this notion, it is interesting to note that secreted CHL1 ectodomain acts as a potent stimulator of neurite outgrowth in vitro (50). Notably, CHL1 interacts with semaphorin 3A during neurite outgrowth and growth cone collapse (53,54). Intriguingly, soluble L1 converts Sema3A-induced axonal repulsion into attraction (55,56).…”
Section: Discussionmentioning
confidence: 83%
“…Recently, Schlatter et al (2007) showed that CHL1 recruits ezrin to the membrane, and that this recruitment contributes to Sema3A induced growth cone collapse. Our data demonstrate that the binding of ERM proteins to Factin is inhibited by Sema3A signaling.…”
Section: Discussionmentioning
confidence: 99%
“…CHL1 has been shown to promote neurite outgrowth of cerebellar and hippocampal neurons, and suppress neuronal cell death. 68,69 In human, deletion or alteration of the CHL1 gene may contribute to mental defects associated with the 3p-syndrome, caused by distal deletions of the short (p) arm of chromosome 3, and schizophrenia. 20,70,71 CHL1-deficient mice have been shown to have aberrant connectivity of hippocampal mossy fibers and olfactory sensory axons, which resulted in behavior change secondary to the disruption of information processing.…”
Section: Synapse and Neurotransmissionmentioning
confidence: 99%